eHalal4All Program—Promoting Halal rural products and services globally by harnessing the Network-of-Mosques (NoM) capabilities - Ahmad Dahlan, Abdul Rahman; Ahmad H.Osman, Rahmah; Ibrahim, Jamaludin; Othman, Mohd Zainudin (Springer Singapore, 2016)

(untitled)
The population of Muslims globally is estimated to be more than 1.6 billion. The recent religious awakening of Muslims and their realization of the importance of compliance with Shari’ah laws in business dealings have enabled them to achieve their economic and well-being goals. This conceptual paper proposes eHalal4All Program, which is proposed to be adopted as one of the 1AZAM Malaysian government-sponsored programs and implemented as a proof-of-concept in raising the economic and social status of rural communities in Sabah, Malaysia. This program has the potential to enhance well-being by providing these rural communities with new skills, machinery, eHalal4All Portal, network of entrepreneurs, and network-of-mosques (NoM) in generating new sources of income. This program is executed based on the deployment of the Quadruple Helix Model (QHM), namely the Government, Academia, Industry, and Citizen. Literature reviews and nine (9) blocks of Business Model Canvas (BMC) framework are used as methodology for this paper. As the extent of rural poverty in Malaysia is expected to be reduced and societal well-being to be enhanced through eHalal4All Program, an added beneﬁt is the minimization of the rural–urban migration process, thus demonstrating the contribution of NoM in realizing partly the meaning of “Rahmatan li’l-Alamin”.